Foodservice management for healthy food choice: factors influencing healthy food choice among university student / Che Amyrisah Che Mei & Norallyna Abdullah - Che Mei, Che Amyrisah; Abdullah, Norallyna (Faculty of Hotel and Tourism, 2017)
Food plays an important role as needed it to keep survive in our life. Sometimes, we share the same choice of food with friends and family ad we also make food as a central part of our celebration. People choose food trough they eat on typical day, price and convenience, mood and sensory appeal, influence by peers, media and also their parents. The consumption of food among university students is determined by themselves. This paper identifies the factors influencing healthy food choice among university students in UiTM Dungun, Terengganu, aim to achieve the two objectives, which are to identify factors influencing healthy food choice among university students and to determine the most influences factors on food choice among university students. Data were collected from a convenient sample of 181 degree students in UiTM Dungun throughout questionnaire by practicing the primary data method. Finding shows that the most chosen food for they eat on typical day was high in fiber with mean score 1.97. For price and convenience of healthy food choice, takes no time to prepare achieve the highest mean score with 1.99 while under the factors of mood and sensory appeal, themost chosen cheers me up with mean score 1.96. For the factors influenced by peers, the higher mean score 2.48 is similar to those consumed by my friends. For factors influenced by media, focus showed in advertisement is the higher mean score with 2.52, while factors influenced healthy food choice by parents the most chosen is preferred by my mother/father with the mean score 1.74. In conclusion, the finding suggests suggest some shed light and rooms for improvement in developing more healthy food for foodservice marketing. Some factors identified can be taken into consideration among foodservice provider to widen more chances towards successful foodservice management in future.